Evaluación técnico financiera del cambio del sistema de levantamiento artificial actual por bombeo hidráulico empleando las condiciones operativas del campo Peguita III (2017)
The Project was developed in Campo Peguita III from Bloque Caracara, initially was made a description of the generalities of the field for showing its history, location and geology of the Cuenca de los Llanos Orientales. After the description of operation of extraction and treatment used in the field, was described the injection net to disposal, performed of dynamic conditions of fluid with the current artificial lift system bear out the energy consumption, was design a hydraulic lift system for the operation conditions, with this, was modeled its dynamic conditions and obtained the requirements for this lifting system, then the comparison between the current and hydraulic lifting systems, in order to the pressure managed actually for the injection of water is the energy supply for the hydraulic lift system.